Extent of adoption gaps in good management practices (GMPs) of shrimp - Kumaran, M; Alagappan, M; Raja, S; Sarada, C; Vimala, D D; Chandrasekaran, V S; Kalaimani, N (Indian Journal of Fisheries, 2011)
Adoption is a mental process through which an individual eventually make a decision to follow an innovation after carefully evaluating its relative advantage, compatibility, complexity, visibility and adoptability vis-Ã -vis his biophysical and socioeconomic environment. An investigation carried out among the shrimp farmers of Andhra Pradesh (AP) and Tamil Nadu (TN) to assess the ’adoption-gap’ in Good Management Practices (GMPs) of shrimp culture has found that about 68 and 72% of the GMPs of shrimp farming were adopted by the farmers of AP and TN and an average adoption gap of 32 and 28% was noticed in AP and TN respectively. Adoption of aquaculture guidelines like Effluent Treatment System (ETS) needs mass education, voluntary cooperation and maximum motivation among the farmers. A strong extension support to facilitate the above is absolutely essential. Further, educational status, occupation, farm size, training, farm experience and social participation of the shrimp farmers aid significantly in minimizing their adoption gap.